Embodiment and representations of beauty - Medina, Esther Hernández; Pozo, Sharina Maíllo (Advances in gender research, 2024)
Beauty embodiment and representations of beauty are crafted by legitimised hierarchies of power in popular culture, including across fashion, sports, media and social media outlets, and the arts. Informed and guided by an intersectional lens with a focus on underrepresented communities, this volume of Advances in Gender Research foregrounds gender and sexuality to engage with beauty as a site of knowledge creation. Interrogating its very definition, chapters take a revolutionary, intersectional approach to explore beauty as an avenue to create alternative knowledge as well as a conduit to engage in critical conversations on race, ethnicity, gender, sexuality, illness, and fitness. Emphasizing that beauty definitions and standards in any given society closely reflect the distribution of power within it, contributors think critically about the role of institutions such as the hair industry, workplaces, the visual arts, and classical dance in how beauty is socially construed and conceptualized. Grounded in a more open-ended conception that goes beyond aesthetics, Embodiment and Representations of Beauty celebrates beauty's capacity as a source of liberation, agency, social justice, decolonization, and survival for marginalized communities, as well as an emancipatory path to feminist liberation.